Effects of physical training and behavioural strategies towards muscle strength and mental health in the elderly - Azliyana Azizan,; Shazana Sahrani,; Asilah Anum,; Nurul Husna,; Rahman, Farid (Penerbit Universiti Kebangsaan Malaysia, 2021)
The promotion of physical training (PT) and positive behavior in the elderly requires effective interventions. This study shows the effect of PT during an 11-week intervention program by applying behavioral strategies. A total of 63 participants aged 65 years old were randomly divided into three groups: Physical with a behavioral group, PB (n=18), Physical group, PG (n=23), and Control group, CG (n=22). PB and PG participants underwent a six-week group-based multi-component PT for one hour per session, three sessions a week. After PT, participants in PB began five-week behavioral exercises for 30 min, twice a week. Meanwhile, CG participants only have to maintain their daily routines. Upper and lower limb muscle strength and mental health were assessed. Results from repeated measures ANOVA showed significant differences between groups due to time factor, group and time interaction, and between-group factor (p<0.05) for Right UL, Left UL, and LL strength. Analysis of covariance (ANCOVA) for mental health [F(2.58) = 33.49] (p<0.05)] showed significant main effects among participants in PB, thus indicating improved mental health. In conclusion, combined of PT and behavioral strategies may be a promising strategy in enhancing better physical and mental well-being of the elderly.